A flame retardant waterborne epoxy coating and its preparation method and application

Through the application of modified nanogenicants in water-based epoxy coatings, the shortcomings of existing water-based epoxy coatings in water-based salt spray resistance are solved, and coatings with high water-resistant, anti-fouling and anti-corrosion properties are achieved, which are suitable for industrial use. Metal anti-corrosion and ship interior cabins.

CN119060615BActive Publication Date: 2025-02-11GUANGDONG WEIQI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411568937.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-11
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

In the field of industrial metal anti-corrosion, the paint film has poor water resistance and salt spray resistance, and the water-based flame retardant coating has generally poor water resistance, which is prone to wrinkling, bubbles and peeling, which limits its application. .

Method used

Using modified nanogenic agents, a flame-retardant aqueous epoxy coating was prepared by combining materials such as ammonium polyphosphate, melamine, pentaerythritol, chloride paraffin and nanotitanium dioxide. Modifying nanogenic agents improve the moisture and heat resistance and flame retardant properties of the coating by forming a carbon layer and a foam layer.

Benefits of technology

It achieves high waterproofness, anti-fouling and anti-corrosion properties of the coating, has good room temperature curing performance and storage stability, has low VOC content, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention proposes a flame retardant waterborne epoxy coating and a preparation method and application thereof, belonging to the technical field of coatings. It comprises component A and component B, wherein the component A is prepared by the following raw materials in parts by weight: 3-4 parts of modified nano agent, 7-10 parts of water, 0.2-0.3 parts of aqueous dispersant, 0.2-0.3 parts of aqueous wetting agent, 0.2-0.3 parts of aqueous defoamer, 3-5 parts of aqueous curing agent, and the component B is prepared by the following raw materials in parts by weight: 12-15 parts of epoxy resin, 1.2-1.5 parts of propylene glycol methyl ether. The flame retardant waterborne epoxy coating prepared by the present invention has good mechanical properties, and the coating has high water resistance, antifouling and anticorrosive properties, weather resistance, UV aging resistance and flame retardancy, good room temperature curing performance, good storage stability, low VOC content, and broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a flame retardant waterborne epoxy coating and a preparation method and application thereof. Background Art

[0002] Epoxy resin coating is one of the most widely used, applicable and important coatings in the world. According to the different curing forms, epoxy resin coatings are mainly divided into: self-drying one-component liquid epoxy coatings, self-drying two-component liquid epoxy coatings, self-drying multi-component liquid epoxy coatings, baking one-component liquid epoxy coatings, baking two-component liquid epoxy coatings, powder epoxy coatings and radiation-cured epoxy coatings. According to the different coating states, epoxy resin coatings are mainly divided into: solvent-based epoxy coatings, solvent-free epoxy coatings and water-based epoxy coatings. According to different uses, epoxy resin coatings are mainly divided into: marking coatings, anti-corrosion coatings, heat-resistant coatings, fire-retardant coatings, temperature-indicating coatings, etc.

[0003] Waterborne epoxy coatings are gaining more and more attention and being used more and more widely due to their advantages in environmental protection and performance. However, their formula is relatively complex, with many types of additives, and many additives may have a significant impact on the performance of the coating. my country started relatively late in the research and development of waterborne epoxy resins. The development of high-end waterborne epoxy emulsions is still mostly in the laboratory stage, and there is a lack of mature products that can be industrialized. Many waterborne epoxy resin emulsions developed by Zhuhai Jili Chemical Enterprise Co., Ltd. have been put into large-scale production, but such products are still difficult to be satisfactory in the field of industrial metal corrosion protection. The outstanding problem is that the paint film has poor water and salt spray resistance, which is far from meeting the most basic corrosion protection requirements. At the same time, the water resistance of waterborne flame retardant coatings is generally poor, and wrinkling, bubbling and peeling are prone to occur, which greatly limits the application of waterborne flame retardant coatings.

[0004] The interior of a ship is a semi-enclosed limited space. During the construction of oil-based paint in the cabin, volatile solvents tend to accumulate in the cabin. When a certain amount is reached, an explosion may occur when encountering an ignition point. In addition, volatile solvents are not good for the health of construction workers, and volatile organic solvents (VOC) are not friendly to the environment. National or international standards require that cabin paint must be flame-retardant, so it is of great significance to develop a flame-retardant water-based epoxy coating with anti-corrosion properties. Summary of the invention

[0005] The purpose of the present invention is to provide a flame retardant water-based epoxy coating and a preparation method and application thereof, which has good mechanical properties, high waterproof, antifouling and anticorrosive properties, weather resistance, UV aging resistance and flame retardancy, good room temperature curing performance, good storage stability, low VOC content, and broad application prospects.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The invention provides a flame retardant waterborne epoxy coating, comprising a component A and a component B. The component A is prepared from the following raw materials in parts by weight: 3-4 parts of a modified nano agent, 7-10 parts of water, 0.2-0.3 parts of an aqueous dispersant, 0.2-0.3 parts of an aqueous wetting agent, 0.2-0.3 parts of an aqueous defoamer, and 3-5 parts of an aqueous curing agent; the component B is prepared from the following raw materials in parts by weight: 12-15 parts of an epoxy resin and 1.2-1.5 parts of propylene glycol methyl ether; the modified nano agent is prepared by hydrolyzing titanium dioxide modified with a silane coupling agent, depositing carbon on the surface, then adding sulfuric acid and potassium permanganate for intercalation, and finally being modified with fluorine-containing silane and aminosilane.

[0008] As a further improvement of the present invention, the aqueous dispersant is 5040, the aqueous wetting agent is PE-100, the aqueous defoamer is BYK-017, the aqueous curing agent is aqueous epoxy curing agent EPIKURE 6870-W-53, and the epoxy resin is epoxy resin 521.

[0009] As a further improvement of the present invention, the modified nanoagent is prepared from the following raw materials in parts by weight: 18-22 parts of ammonium polyphosphate, 10-12 parts of melamine, 7-9 parts of pentaerythritol, 2-4 parts of chlorinated paraffin-42, and 10-15 parts of modified nanoagent.

[0010] As a further improvement of the present invention, the preparation method of the modified nanoagent is as follows:

[0011] S1. Preparation of nano titanium dioxide: tetrabutyl titanate was dissolved in ethanol, water and ammonia were added, the reaction was stirred, centrifuged, washed, dried, and calcined to obtain nano titanium dioxide;

[0012] S2. Preparation of modified nano-titanium dioxide: dissolving a silane coupling agent in ethanol, adding nano-titanium dioxide, heating and stirring to react, centrifuging, washing, and drying to obtain modified nano-titanium dioxide;

[0013] S3. Hydrolysis: adding the modified nano-titanium dioxide to water, heating for hydrolysis, centrifuging, washing, drying, and calcining to obtain coated nano-titanium dioxide;

[0014] S4. Carbon deposition: The coated nano-titanium dioxide was heated under inert gas protection, hydrogen and n-hexane were introduced, the reaction was kept warm, and the temperature was lowered to room temperature to obtain carbon-deposited nano-titanium dioxide;

[0015] S5. Intercalation: adding the carbon deposition coated nano-titanium dioxide to water, adding sulfuric acid and potassium permanganate, stirring the reaction, centrifuging, washing, and drying to obtain expanded carbon deposition coated nano-titanium dioxide;

[0016] S6. Preparation of modified nano-agent: adding expanded carbon deposition coated nano-titanium dioxide into ethanol, adding fluorine-containing silane and aminosilane, heating and stirring to react, centrifuging, washing, and drying to obtain the modified nano-agent.

[0017] As a further improvement of the present invention, the mass ratio of tetrabutyl titanate, ethanol, water and ammonia water in step S1 is 10-12:90-120:8-10:1-2, the stirring reaction time is 2-3h, the calcination temperature is 400-500°C, and the time is 1-2h; the silane coupling agent in step S2 is selected from at least one of KH550, KH602 and KH702, the mass ratio of the silane coupling agent to nano-titanium dioxide is 3-4:10, the heating stirring reaction temperature is 40-50°C, and the time is 1-2h.

[0018] As a further improvement of the present invention, the temperature of the heating hydrolysis in step S3 is 80-90°C, the time is 30-50min, the temperature of the calcination is 400-500°C, and the time is 1-2h; the ventilation rates of hydrogen and n-hexane in step S4 are 90-110mL / min and 1-2mL / min respectively, and the heating to 600-700°C is for 30-50min.

[0019] As a further improvement of the present invention, the mass ratio of the carbon deposition coated nano-titanium dioxide, sulfuric acid and potassium permanganate in step S5 is 10:30-50:0.5-1, the concentration of the sulfuric acid is 70-80wt%, and the stirring reaction time is 0.5-1h; the mass ratio of the expanded carbon deposition coated nano-titanium dioxide, fluorine-containing silane and aminosilane in step S6 is 10:2-3:1-2, the temperature of the heating stirring reaction is 40-50°C, the time is 1-2h, and the fluorine-containing silane is selected from 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyl trimethoxysilane, dodecafluoroheptyl propyl trimethoxysilane, dodecafluoroheptyl propyl The aminosilane is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane and diethylenetriaminepropyltrimethoxysilane.

[0020] The present invention further protects a method for preparing the above-mentioned flame retardant waterborne epoxy coating, comprising the following steps:

[0021] (1) ammonium polyphosphate, melamine, pentaerythritol, chlorinated paraffin-42 and modified nano-agent are uniformly mixed to prepare modified nano-agent;

[0022] (2) Evenly mixing epoxy resin and propylene glycol methyl ether to prepare component B;

[0023] (3) Adding an aqueous dispersant, an aqueous wetting agent, an aqueous defoaming agent, and an aqueous curing agent into water, adding a modified nano-agent, dispersing at high speed, and grinding to obtain component A;

[0024] When in use, component A and component B are mixed evenly, applied to the surface of the substrate, and cured at room temperature to obtain a coating.

[0025] As a further improvement of the present invention, the rotation speed of the high-speed dispersion is 1000-1200 r / min, the time is 20-30 min, and the grinding is performed to a fineness of <100 μm.

[0026] The present invention further protects the use of the above-mentioned flame-retardant water-based epoxy coating in the interior cabin of a ship.

[0027] The present invention has the following beneficial effects:

[0028] The invention prepares a modified nano agent, which comprises ammonium polyphosphate, melamine, pentaerythritol, chlorinated paraffin-42, and the modified nano agent. The ammonium polyphosphate begins to decompose at about 290°C and releases NH3 and phosphoric acid. The phosphoric acid dehydrates and carbonizes the hydroxyl groups on the pentaerythritol to form a uniform and dense three-dimensional spatial structure carbonized layer, reduces the generation of combustible tar, aldehydes, and ketones during thermal decomposition, promotes the generation of non-combustible gas, and simultaneously prevents carbon oxidation reaction with large heat release, improves the quality of the carbonaceous layer of the coating, enhances the moisture and heat resistance of the coating, and avoids the occurrence of salting out. Pentaerythritol is the skeleton basis for forming a three-dimensional spatial structure foam carbonaceous layer, and esterifies with phosphoric acid, metaphosphoric acid, and pyrophosphoric acid released by the ammonium polyphosphate in the gas phase under high temperature conditions, dehydrates and carbonizes the hydroxyl groups on the pentaerythritol to form a foam carbonaceous layer. When melamine meets fire and reaches a certain temperature, it decomposes and releases non-combustible gases, such as ammonia, water, carbon dioxide, and hydrogen halide, which causes the coating to foam and expand under the condition of reaching the softening point, forming a sponge-like carbonized layer, achieving heat insulation and flame retardant effects. When the temperature of chlorinated paraffin rises to about 220°C, the base resin begins to soften, and chlorinated paraffin begins to decompose at about 210°C, releasing CH4 and HCl gases, causing the softened coating to begin to foam. At the same time, HCl gas also has a flame retardant effect.

[0029] The modified nano-agent is a nano-modified nano-agent with nano titanium dioxide as the core and an expanded carbon layer coated on the surface. When the nano TiO2 is burned at high temperature, it participates in the carbonaceous layer formed by the modified expansion system and generates white TiP2O7, which helps to prevent oxygen from diffusing to the substrate at high temperature, prevents the carbonaceous layer from cracking, and improves the strength of the carbonaceous layer. At the same time, the ultraviolet aging resistance and water resistance of the fireproof coating can also be improved. In the present invention, the carbon layer with the surface expanded is heated and expanded at about 180°C, and the volume of the "scale"-shaped carbon body increases by hundreds of times and becomes a "worm"-shaped carbon body. This physical process is an endothermic process, and because the density of the "worm"-shaped carbon body is relatively small, and the generated expansion product has good stability, it covers the surface of the substrate to keep the effective skeleton component of the foaming layer, thereby playing the role of absorbing heat and reinforcing fibers in the foaming layer, and the foaming layer is evenly heated to achieve the purpose of long-term stable heat insulation.

[0030] The surface of nano-titanium dioxide is coated with a layer of silicon oxide, which can improve the material's water resistance, flame retardancy and mechanical properties, and can also protect titanium dioxide from being decomposed by acid, thereby facilitating the subsequent carbon deposition.

[0031] Compared with separately adding nano titanium dioxide and expanded graphite, the present invention organically combines the two into an integrated structure, which is convenient for simultaneous heat insulation and better formation of a carbonaceous layer, has a faster response speed, can better play a flame retardant effect, can quickly insulate, and prevent further combustion of the substrate.

[0032] In addition, the surface of the prepared expanded carbon deposition coated nano titanium dioxide is modified by aminosilane and fluorine-containing silane. On the one hand, the amino group can react with the epoxy group, so that the modified nano agent is better and more evenly distributed in the epoxy resin substrate, and the compatibility is improved, thereby improving the mechanical properties and flame retardant properties of the coating. On the other hand, the introduction of fluorine-containing silane improves the waterproofness, antifouling and anticorrosion properties of the coating, thereby helping to prepare a waterproof, anticorrosive, antifouling and fireproof coating.

[0033] The flame retardant waterborne epoxy coating prepared by the present invention has good mechanical properties, high waterproof, antifouling and anticorrosive properties, weather resistance, UV aging resistance and flame retardancy, good room temperature curing performance, good storage stability, low VOC content, and broad application prospects. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Preparation Example 1 Preparation of modified nanoagent

[0036] The following steps are involved:

[0037] S1. Preparation of nano titanium dioxide: 10 g of tetrabutyl titanate was dissolved in 90 g of ethanol, 8 g of water and 1 g of ammonia water were added, the mixture was stirred for 2 h, centrifuged, washed, dried, and calcined at 400 ° C for 1 h to obtain nano titanium dioxide;

[0038] S2. Preparation of modified nano-titanium dioxide: 3 g of silane coupling agent KH550 was dissolved in 200 mL of ethanol, 10 g of nano-titanium dioxide was added, the mixture was heated to 40° C., stirred for reaction for 1 h, centrifuged, washed, and dried to obtain modified nano-titanium dioxide;

[0039] S3. Hydrolysis: 10 g of modified nano-titanium dioxide was added to 200 mL of water, heated to 80 ° C, hydrolyzed for 30 min, centrifuged, washed, dried, and calcined at 400 ° C for 1 h to obtain coated nano-titanium dioxide;

[0040] S4. Carbon deposition: The coated nano-titanium dioxide was heated to 600°C under nitrogen protection, and hydrogen and n-hexane were introduced at a flow rate of 90 mL / min and 1 mL / min, respectively. The reaction was kept warm for 30 minutes and then cooled to room temperature to obtain carbon-deposited nano-titanium dioxide;

[0041] S5 intercalation: 10g of carbon deposition coated nano-titanium dioxide was added to 50mL of water, 30g of 70wt% sulfuric acid and 0.5g of potassium permanganate were added, the reaction was stirred for 0.5h, centrifuged, washed, and dried to obtain expanded carbon deposition coated nano-titanium dioxide;

[0042] S6. Preparation of modified nanoagent: 10 g of expanded carbon deposition coated nano-titanium dioxide was added to 200 mL of ethanol, 2 g of dodecafluoroheptylpropyltrimethoxysilane and 1 g of diethylenetriaminepropyltrimethoxysilane were added, heated to 40° C., stirred for reaction for 1 h, centrifuged, washed, and dried to obtain the modified nanoagent.

[0043] Preparation Example 2 Preparation of modified nanoagent

[0044] The following steps are involved:

[0045] S1. Preparation of nano titanium dioxide: 12 g of tetrabutyl titanate was dissolved in 120 g of ethanol, 10 g of water and 2 g of ammonia water were added, the mixture was stirred for 3 h, centrifuged, washed, dried, and calcined at 500 ° C for 2 h to obtain nano titanium dioxide;

[0046] S2. Preparation of modified nano-titanium dioxide: 4 g of silane coupling agent KH550 was dissolved in 200 mL of ethanol, 10 g of nano-titanium dioxide was added, the mixture was heated to 50° C., stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified nano-titanium dioxide;

[0047] S3. Hydrolysis: 10 g of modified nano-titanium dioxide was added to 200 mL of water, heated to 90 ° C, hydrolyzed for 50 min, centrifuged, washed, dried, and calcined at 500 ° C for 2 h to obtain coated nano-titanium dioxide;

[0048] S4. Carbon deposition: The coated nano-titanium dioxide was heated to 700°C under nitrogen protection, and hydrogen and n-hexane were introduced at a flow rate of 110 mL / min and 2 mL / min, respectively. The reaction was kept warm for 50 minutes and then cooled to room temperature to obtain carbon-deposited nano-titanium dioxide;

[0049] S5 intercalation: 10g of carbon deposition coated nano-titanium dioxide was added to 50mL of water, 50g of 80wt% sulfuric acid and 1g of potassium permanganate were added, the reaction was stirred for 1h, centrifuged, washed, and dried to obtain expanded carbon deposition coated nano-titanium dioxide;

[0050] S6. Preparation of modified nanoagent: Add 10 g of expanded carbon deposition coated nano-titanium dioxide into 200 mL of ethanol, add 3 g of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane and 2 g of N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, heat to 50°C, stir to react for 2 h, centrifuge, wash, and dry to obtain the modified nanoagent.

[0051] Preparation Example 3 Preparation of modified nanoagent

[0052] The following steps are involved:

[0053] S1. Preparation of nano titanium dioxide: 11 g of tetrabutyl titanate was dissolved in 100 g of ethanol, 9 g of water and 1.5 g of ammonia water were added, the mixture was stirred for 2.5 h, centrifuged, washed, dried, and calcined at 450° C. for 1.5 h to obtain nano titanium dioxide;

[0054] S2. Preparation of modified nano-titanium dioxide: 3.5 g of silane coupling agent KH550 was dissolved in 200 mL of ethanol, 10 g of nano-titanium dioxide was added, the mixture was heated to 45° C., stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain modified nano-titanium dioxide;

[0055] S3. Hydrolysis: 10 g of modified nano-titanium dioxide was added to 200 mL of water, heated to 85 ° C, hydrolyzed for 40 min, centrifuged, washed, dried, and calcined at 450 ° C for 1.5 h to obtain coated nano-titanium dioxide;

[0056] S4. Carbon deposition: The coated nano-titanium dioxide was heated to 650°C under nitrogen protection, and hydrogen and n-hexane were introduced at a flow rate of 100 mL / min and 1.5 mL / min, respectively. The reaction was kept warm for 40 minutes and then cooled to room temperature to obtain carbon-deposited nano-titanium dioxide;

[0057] S5 intercalation: 10g of carbon deposition coated nano-titanium dioxide was added to 50mL of water, 40g of 75wt% sulfuric acid and 0.7g of potassium permanganate were added, the reaction was stirred for 1h, centrifuged, washed, and dried to obtain expanded carbon deposition coated nano-titanium dioxide;

[0058] S6. Preparation of modified nanoagent: 10 g of expanded carbon deposition coated nano-titanium dioxide was added to 200 mL of ethanol, 2.5 g of dodecafluoroheptylpropylmethyldimethoxysilane and 1.5 g of γ-aminopropyltrimethoxysilane were added, heated to 45° C., stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain a modified nanoagent.

[0059] Comparative Preparation Example 1

[0060] Compared with Preparation Example 3, the difference is that steps S4 and S5 are not performed.

[0061] The details are as follows:

[0062] S1. Preparation of nano titanium dioxide: 11 g of tetrabutyl titanate was dissolved in 100 g of ethanol, 9 g of water and 1.5 g of ammonia water were added, the mixture was stirred for 2.5 h, centrifuged, washed, dried, and calcined at 450° C. for 1.5 h to obtain nano titanium dioxide;

[0063] S2. Preparation of modified nano-titanium dioxide: 3.5 g of silane coupling agent KH550 was dissolved in 200 mL of ethanol, 10 g of nano-titanium dioxide was added, the mixture was heated to 45° C., stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain modified nano-titanium dioxide;

[0064] S3. Hydrolysis: 10 g of modified nano-titanium dioxide was added to 200 mL of water, heated to 85 ° C, hydrolyzed for 40 min, centrifuged, washed, dried, and calcined at 450 ° C for 1.5 h to obtain coated nano-titanium dioxide;

[0065] S4. Preparation of modified nanoagent: 10 g coated nano titanium dioxide was added to 200 mL ethanol, 2.5 g dodecafluoroheptylpropylmethyldimethoxysilane and 1.5 g γ-aminopropyltrimethoxysilane were added, heated to 45°C, stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain the modified nanoagent.

[0066] Comparative Preparation Example 2

[0067] Compared with Preparation Example 3, the difference is that step S6 is not performed.

[0068] The details are as follows:

[0069] S1. Preparation of nano titanium dioxide: 11 g of tetrabutyl titanate was dissolved in 100 g of ethanol, 9 g of water and 1.5 g of ammonia water were added, the mixture was stirred for 2.5 h, centrifuged, washed, dried, and calcined at 450° C. for 1.5 h to obtain nano titanium dioxide;

[0070] S2. Preparation of modified nano-titanium dioxide: 3.5 g of silane coupling agent KH550 was dissolved in 200 mL of ethanol, 10 g of nano-titanium dioxide was added, the mixture was heated to 45° C., stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain modified nano-titanium dioxide;

[0071] S3. Hydrolysis: 10 g of modified nano-titanium dioxide was added to 200 mL of water, heated to 85 ° C, hydrolyzed for 40 min, centrifuged, washed, dried, and calcined at 450 ° C for 1.5 h to obtain coated nano-titanium dioxide;

[0072] S4. Carbon deposition: The coated nano-titanium dioxide was heated to 650°C under nitrogen protection, and hydrogen and n-hexane were introduced at a flow rate of 100 mL / min and 1.5 mL / min, respectively. The reaction was kept warm for 40 minutes and then cooled to room temperature to obtain carbon-deposited nano-titanium dioxide;

[0073] S5. Intercalation: 10 g of carbon deposition coated nano titanium dioxide was added to 50 mL of water, and 40 g of 75 wt% sulfuric acid and 0.7 g of potassium permanganate were added. The mixture was stirred for 1 h, centrifuged, washed, and dried to obtain expanded carbon deposition coated nano titanium dioxide, which is the modified nanoagent.

[0074] Comparative Preparation Example 3

[0075] Compared with Preparation Example 3, the difference is that dodecafluoroheptylpropylmethyldimethoxysilane is not added in step S6.

[0076] The details are as follows:

[0077] S6. Preparation of modified nano-agent: 10 g of expanded carbon deposition coated nano-titanium dioxide was added to 200 mL of ethanol, 4 g of γ-aminopropyltrimethoxysilane was added, heated to 45° C., stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain a modified nano-agent.

[0078] Comparative Preparation Example 4

[0079] Compared with Preparation Example 3, the difference is that γ-aminopropyltrimethoxysilane is not added in step S6.

[0080] The details are as follows:

[0081] S6. Preparation of modified nanoagent: 10 g of expanded carbon deposition coated nano titanium dioxide was added to 200 mL of ethanol, 4 g of dodecafluoroheptylpropylmethyldimethoxysilane was added, heated to 45° C., stirred for reaction for 1.5 h, centrifuged, washed, and dried to obtain a modified nanoagent.

[0082] Example 1

[0083] The present embodiment provides a flame-retardant water-based epoxy coating, including component A and component B, wherein component A is prepared from the following raw materials in parts by weight: 3 parts of modified nano agent, 7 parts of water, 0.2 parts of water-based dispersant 5040, 0.2 parts of water-based wetting agent PE-100, 0.2 parts of water-based defoamer BYK-017, and 3 parts of water-based epoxy curing agent EPIKURE 6870-W-53, and component B is prepared from the following raw materials in parts by weight: 12 parts of epoxy resin 521 and 1.2 parts of propylene glycol methyl ether.

[0084] The modified nano agent is prepared from the following raw materials in parts by weight: 18 parts of ammonium polyphosphate, 10 parts of melamine, 7 parts of pentaerythritol, 2 parts of chlorinated paraffin-42, and 10 parts of modified nano agent.

[0085] The preparation method comprises the following steps:

[0086] (1) ammonium polyphosphate, melamine, pentaerythritol, chlorinated paraffin-42, and the modified nanoagent prepared in Preparation Example 1 are uniformly mixed to prepare a modified nanoagent;

[0087] (2) Evenly mixing epoxy resin and propylene glycol methyl ether to prepare component B;

[0088] (3) Add an aqueous dispersant, an aqueous wetting agent, an aqueous defoaming agent, and an aqueous curing agent into water, add the modified nano-agent, stir and disperse at 1000 r / min for 20 min, grind to a fineness of <100 μm, and obtain component A;

[0089] When in use, component A and component B are mixed evenly, applied to the surface of the substrate, and cured at room temperature to obtain a coating.

[0090] Example 2

[0091] The present embodiment provides a flame-retardant water-based epoxy coating, including component A and component B, wherein component A is prepared from the following raw materials in parts by weight: 4 parts of modified nano agent, 10 parts of water, 0.3 parts of water-based dispersant 5040, 0.3 parts of water-based wetting agent PE-100, 0.3 parts of water-based defoamer BYK-017, and 5 parts of water-based epoxy curing agent EPIKURE 6870-W-53, and component B is prepared from the following raw materials in parts by weight: 15 parts of epoxy resin 521 and 1.5 parts of propylene glycol methyl ether.

[0092] The modified nano agent is prepared from the following raw materials in parts by weight: 22 parts of ammonium polyphosphate, 12 parts of melamine, 9 parts of pentaerythritol, 4 parts of chlorinated paraffin-42, and 15 parts of the modified nano agent.

[0093] The preparation method comprises the following steps:

[0094] (1) ammonium polyphosphate, melamine, pentaerythritol, chlorinated paraffin-42, and the modified nanoagent prepared in Preparation Example 1 are uniformly mixed to prepare a modified nanoagent;

[0095] (2) Evenly mixing epoxy resin and propylene glycol methyl ether to prepare component B;

[0096] (3) Add an aqueous dispersant, an aqueous wetting agent, an aqueous defoamer, and an aqueous curing agent into water, add the modified nano-agent, stir and disperse at 1200 r / min for 30 min, and grind to a fineness of <100 μm to obtain component A;

[0097] When in use, component A and component B are mixed evenly, applied to the surface of the substrate, and cured at room temperature to obtain a coating.

[0098] Example 3

[0099] The present embodiment provides a flame-retardant water-based epoxy coating, including component A and component B, wherein component A is prepared from the following raw materials in parts by weight: 3.5 parts of modified nano agent, 8 parts of water, 0.25 parts of water-based dispersant 5040, 0.25 parts of water-based wetting agent PE-100, 0.25 parts of water-based defoamer BYK-017, and 4 parts of water-based epoxy curing agent EPIKURE 6870-W-53, and component B is prepared from the following raw materials in parts by weight: 13 parts of epoxy resin 521 and 1.3 parts of propylene glycol methyl ether.

[0100] The modified nano agent is prepared from the following raw materials in parts by weight: 20 parts of ammonium polyphosphate, 11 parts of melamine, 8 parts of pentaerythritol, 3 parts of chlorinated paraffin-42, and 12 parts of modified nano agent.

[0101] The preparation method comprises the following steps:

[0102] (1) ammonium polyphosphate, melamine, pentaerythritol, chlorinated paraffin-42, and the modified nanoagent prepared in Preparation Example 3 are uniformly mixed to prepare a modified nanoagent;

[0103] (2) Evenly mixing epoxy resin and propylene glycol methyl ether to prepare component B;

[0104] (3) Add an aqueous dispersant, an aqueous wetting agent, an aqueous defoamer, and an aqueous curing agent into water, add a modified nano-agent, stir and disperse at 1100 r / min for 25 min, and grind to a fineness of <100 μm to obtain component A;

[0105] When in use, component A and component B are mixed evenly, applied to the surface of the substrate, and cured at room temperature to obtain a coating.

[0106] Comparative Example 1

[0107] Compared with Example 3, the difference is that the modified nanoagent is prepared by Comparative Preparation Example 1.

[0108] Comparative Example 2

[0109] Compared with Example 3, the difference is that the modified nanoagent is prepared by Comparative Preparation Example 2.

[0110] Comparative Example 3

[0111] Compared with Example 3, the difference is that the modified nanoagent is prepared by Comparative Preparation Example 3.

[0112] Comparative Example 4

[0113] Compared with Example 3, the difference is that the modified nanoagent is prepared by Comparative Preparation Example 4.

[0114] Comparative Example 5

[0115] Compared with Example 3, the difference is that no modified nano agent is added.

[0116] Test Example 1

[0117] The components A and B of the flame-retardant waterborne epoxy coatings prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention were mixed uniformly in a mass ratio of 1:3, and scraped according to GB / T 1727, with the coating thickness controlled to be 0.5 mm, and the coating thickness was measured according to GB / T 13452.2. After the test plate was prepared, the test plate was placed for 7 days under the conditions specified in GB / T 9278 before testing.

[0118] The results are shown in Tables 1 and 2.

[0119] Table 1

[0120] Group Limiting oxygen index (%) Adhesion (grade) Flexibility (mm) Impact strength (kg cm) Test Standards GB / T 2406.2-2009 GB / T 9286-2021 GB / T 1748-1979 GB / T 1732-2020 Example 1 36.2 1 0.05 62 Example 2 36.4 1 0.03 60 Example 3 36.5 1 0.02 65 Comparative Example 1 31.2 1 0.09 58 Comparative Example 2 30.7 2 0.17 50 Comparative Example 3 34.7 1 0.10 55 Comparative Example 4 32.6 2 0.14 53 Comparative Example 5 28.2 2 0.27 42

[0121] Table 2

[0122] Group Seawater resistance Freeze-thaw resistance (times) Water resistance Test Standards GB / T 1733-1993 GB / T 9268-2008 Method A GB / T 1733–1993 Example 1 After immersion for 12 months, the coating did not bubble, crack or fall off 15 After immersion for 12 months, the coating did not bubble, crack or fall off Example 2 After immersion for 12 months, the coating did not bubble, crack or fall off 14 After immersion for 12 months, the coating did not bubble, crack or fall off Example 3 After immersion for 12 months, the coating did not bubble, crack or fall off 17 After immersion for 12 months, the coating did not bubble, crack or fall off Comparative Example 1 After immersion for 12 months, the coating did not bubble, crack or fall off 13 After immersion for 12 months, the coating did not bubble, crack or fall off Comparative Example 2 After 6 months of immersion, the coating bubbled, cracked and fell off 9 After 9 months of immersion, the coating bubbled, cracked and fell off Comparative Example 3 After 9 months of immersion, the coating bubbled, cracked and fell off 12 After 10 months of immersion, the coating bubbled, cracked and fell off Comparative Example 4 After 10 months of immersion, the coating bubbled, cracked and fell off 10 After 11 months of immersion, the coating bubbled, cracked and fell off Comparative Example 5 After immersion for 1 month, the coating bubbled, cracked and fell off 6 After immersion for 3 months, the coating bubbled, cracked and fell off

[0123] It can be seen from the above table that the flame retardant waterborne epoxy coatings prepared in Examples 1-3 of the present invention have good comprehensive properties.

[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A flame retardant waterborne epoxy coating, characterized in that: The invention comprises component A and component B, wherein the component A is prepared from the following raw materials in parts by weight: 3-4 parts of modified nano agent A, 7-10 parts of water, 0.2-0.3 parts of aqueous dispersant, 0.2-0.3 parts of aqueous wetting agent, 0.2-0.3 parts of aqueous defoamer, and 3-5 parts of aqueous curing agent; the component B is prepared from the following raw materials in parts by weight: 12-15 parts of epoxy resin and 1.2-1.5 parts of propylene glycol methyl ether; the modified nano agent A is prepared from the following raw materials in parts by weight: 18-22 parts of ammonium polyphosphate, 10-12 parts of melamine, 3-5 parts of pentaerythritol, 2-4 parts of chlorinated paraffin-42, and the modified nano agent B. 10-15 parts; the modified nanoagent B is prepared by hydrolyzing titanium dioxide modified with a silane coupling agent, depositing carbon on the surface, then adding sulfuric acid and potassium permanganate for intercalation, and finally modifying with fluorine-containing silane and aminosilane.

2. The flame retardant waterborne epoxy coating according to claim 1, characterized in that: The water-based dispersant is 5040, the water-based wetting agent is PE-100, the water-based defoaming agent is BYK-017, the water-based curing agent is water-based epoxy curing agent EPIKURE 6870-W-53, and the epoxy resin is epoxy resin 521.

3. The flame retardant waterborne epoxy coating according to claim 1, characterized in that: The preparation method of the modified nanoagent B is as follows: S1. Preparation of nano titanium dioxide: tetrabutyl titanate was dissolved in ethanol, water and ammonia were added, the reaction was stirred, centrifuged, washed, dried, and calcined to obtain nano titanium dioxide; S2. Preparation of modified nano-titanium dioxide: dissolving a silane coupling agent in ethanol, adding nano-titanium dioxide, heating and stirring to react, centrifuging, washing, and drying to obtain modified nano-titanium dioxide; S3. Hydrolysis: adding the modified nano-titanium dioxide to water, heating for hydrolysis, centrifuging, washing, drying, and calcining to obtain coated nano-titanium dioxide; S4. Carbon deposition: The coated nano-titanium dioxide was heated under an inert gas protection, hydrogen and n-hexane were introduced, the reaction was kept warm, and the temperature was lowered to room temperature to obtain carbon-deposited nano-titanium dioxide; S5. Intercalation: adding the carbon deposition coated nano-titanium dioxide to water, adding sulfuric acid and potassium permanganate, stirring the reaction, centrifuging, washing, and drying to obtain expanded carbon deposition coated nano-titanium dioxide; S6. Preparation of modified nanoagent B: adding expanded carbon deposition coated nano titanium dioxide into ethanol, adding fluorine-containing silane and aminosilane, heating and stirring to react, centrifuging, washing, and drying to obtain modified nanoagent B.

4. The flame retardant waterborne epoxy coating according to claim 3, characterized in that: In step S1, the mass ratio of tetrabutyl titanate, ethanol, water and ammonia water is 10-12:90-120:8-10:1-2, the stirring reaction time is 2-3 hours, the calcination temperature is 400-500°C, and the time is 1-2 hours; in step S2, the silane coupling agent is selected from at least one of KH550, KH602 and KH702, the mass ratio of the silane coupling agent to nano-titanium dioxide is 3-4:10, the heating stirring reaction temperature is 40-50°C, and the time is 1-2 hours.

5. The flame retardant waterborne epoxy coating according to claim 3, characterized in that: The temperature of the heating hydrolysis in step S3 is 80-90°C, the time is 30-50min, the temperature of the calcination is 400-500°C, and the time is 1-2h; the ventilation rates of hydrogen and n-hexane in step S4 are 90-110mL / min and 1-2mL / min respectively, and the heating to 600-700°C is for 30-50min.

6. The flame retardant waterborne epoxy coating according to claim 3, characterized in that: The mass ratio of the carbon deposition coated nano-titanium dioxide, sulfuric acid and potassium permanganate in step S5 is 10:30-50:0.5-1, the concentration of the sulfuric acid is 70-80wt%, and the stirring reaction time is 0.5-1h; the mass ratio of the expanded carbon deposition coated nano-titanium dioxide, fluorinated silane and aminosilane in step S6 is 10:2-3:1-2, the temperature of the heating stirring reaction is 40-50°C, the time is 1-2h, and the fluorinated silane is selected from 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyl trimethoxysilane, dodecafluoroheptyl propyl trimethoxysilane, dodecafluoroheptyl propyl methyl dimethoxysilane, The aminosilane is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane and diethylenetriaminepropyltrimethoxysilane.

7. A method for preparing a flame retardant waterborne epoxy coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) ammonium polyphosphate, melamine, pentaerythritol, chlorinated paraffin-42 and modified nanoagent B are uniformly mixed to prepare modified nanoagent A; (2) Evenly mixing epoxy resin and propylene glycol methyl ether to prepare component B; (3) Adding an aqueous dispersant, an aqueous wetting agent, an aqueous defoaming agent, and an aqueous curing agent into water, adding the modified nanoagent A, dispersing at high speed, and grinding to obtain component A; When in use, component A and component B are mixed evenly, applied to the surface of the substrate, and cured at room temperature to obtain a coating.

8. The preparation method according to claim 7, characterized in that: The high-speed dispersion has a rotation speed of 1000-1200 r / min and a time of 20-30 min, and the grinding is performed to a fineness of <100 μm.

9. Use of the flame-retardant waterborne epoxy coating according to any one of claims 1 to 6 in a ship's interior cabin.

Citation Information

Patent Citations

  • Method for preparing high fire resistance property expandable graphite

    CN101100297A

  • Method for preparing composition of carbon nano tube and graphene by using sheet material

    CN102674316A